Deliberative Mapping of options for tackling climate change: Citizens and specialists 'open up' appraisal of geoengineering. (April 2016) - Bellamy, Rob; Chilvers, Jason; Vaughan, Naomi E.
Appraisals of deliberate, large-scale interventions in the earth's climate system, known collectively as 'geoengineering', have largely taken the form of narrowly framed and exclusive expert analyses that prematurely 'close down' upon particular proposals. Here, we present the findings from the first 'upstream' appraisal of geoengineering to deliberately 'open up' to a broader diversity of framings, knowledges and future pathways. We report on the citizen strand of an innovative analytic–deliberative participatory appraisal process called Deliberative Mapping. A select but diverse group of sociodemographically representative citizens from Norfolk (United Kingdom) were engaged in a deliberative multi-criteria appraisal of geoengineering proposals relative to other options for tackling climate change, in parallel to symmetrical appraisals by diverse experts and stakeholders. Despite seeking to map divergent perspectives, a remarkably consistent view of option performance emerged across both the citizens' and the specialists' deliberations, where geoengineering proposals were outperformed by mitigation alternatives.